Meningkatkan Aktivitas Dan Hasil Belajar Matematika Siswa Kelas IV SDN 6 Baamang Tengah Dengan Metode Penugasan Dan Latihan 2021/2022 - Karlimansyah Karlimansyah (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This research was motivated by students who have good achievement in learning only 12 students out of 21 students who scored above 60 at SDN 6 Baamang Tengah, Baamang District. This is caused by the lack of active students and the lack of student interest in learning which results in low student achievement results. The purpose of this research is to increase students' learning creativity in the material of Multiplication Count Operation with assignments to students. The research was carried out in three cycles, the planning stage, the implementation and observation stage, the reflection stage and the revision stage. From the observations of colleagues, it was obtained that there was an increase in data with a significant increase in the learning process in the second cycle using the Assignment and Exercise method compared to the learning process in the first cycle which only used the lecture method, namely in the initial cycle the average value of learning reached 53, 20. Meanwhile in the first cycle the average value of learning reached 65.23. In the second cycle, the learning average reached 77.38. In the third cycle, the learning average reached 92.38.